Defect Engineering Enables Synergistic Action of Enzyme-Mimicking Active Centers for High-Efficiency Tumor Therapy - Yu, Bin; Wang, Wei; Sun, Wenbo; Jiang, Chunhuan; Lu, Lehui (Journal of the American Chemical Society, 2021)
Perusing redox nanozymes capable of disrupting cellular homeostasis offers new opportunities to develop cancer-specific therapy, but remains challenging, because most artificial enzymes lack enzyme-like scale and configuration. Herein, for the first time, we leverage a defect engineering strategy to develop a simple yet efficient redox nanozyme by constructing enzyme-mimicking active centers and investigated its formation and catalysis mechanism thoroughly. Specifically, the partial Fe doping in MoO (donated as Fe-MoO ) was demonstrated to activate structure reconstruction with abundant defect site generation, including Fe substitution and oxygen vacancy (OV) defects, which significantly enable the binding capacity and catalytic activity of Fe-MoO nanozymes in a synergetic fashion. More intriguingly, plenty of delocalized electrons appear due to Fe-facilitated band structure reconstruction, directly contributing to the remarkable surface plasmon resonance effect in the near-infrared (NIR) region. Under NIR-II laser irradiation, the designed Fe-MoO nanozymes are able to induce substantial disruption of redox and metabolism homeostasis in the tumor region via enzyme-mimicking cascade reactions, thus significantly augmenting therapeutic effects. This study that takes advantage of defect engineering offers new insights into developing high-efficiency redox nanozymes.